2015
DOI: 10.5539/ijef.v7n5p82
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Foreign Direct Investments: Dynamic Panel Data Evidence

Abstract: This paper examines the determinants of foreign direct investment (FDI) for 88 countries in the 1985-2011 period, using a static and dynamic panel data analysis. The results show that urbanization rate, the ratio of population over the age of 65, social security spending and health spending have a negative and statistically significant impact on FDI, while per capita GDP, GDP growth, market size, inflation rate, unemployment rate, labor force growth, credit to private sector, market capitalization and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 61 publications
(93 reference statements)
2
17
0
3
Order By: Relevance
“…(1) large consumer market for both domestic and foreign products which can lead to an inflow of foreign direct investments (Bell et al, 2015;Erdogan and Unver, 2015;Nauman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(1) large consumer market for both domestic and foreign products which can lead to an inflow of foreign direct investments (Bell et al, 2015;Erdogan and Unver, 2015;Nauman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several studies have examined the consequence of corruption on FDI inflow with most of the outcomes supporting the gabbing hand view, while some works have validated the helping hand view and few others found insignificant relationship. For instance, studies such as Fung and Gracia-Herrero (2012), Dauti (2015), De Beule and Duanmu (2012), Amarandei (2013), Aziz and Mishra (2015), Júlio, Pinheiro-Alves and Tavares (2013), Al-Khouri and Khalik (2013), Kasasbeh, Mdanat and Khasawneh (2018), Osabutey and Okoro (2015), Ferreira and Ferreira (2016), Abala (2014), Ajide and Raheem (2016), Nnadi and Soobaroyen (2015), Epaphra and Massawe (2017), Jeong (2014), Quazi (2014), Azam and Ahmad (2013), Mathur and Singh (2013), Hossain and Rahman (2017), Castro and Nunes (2013), Morrissey and Udomkerdmongkol (2012), Kurul andYalta (2017), Hayakawa, Kimuri andLee (2013), Alemu (2012), Kimura and Lee (2013), Erdogan and Unver (2015), Hossain (2016), Udenze (2014) and Jalil, Qureshi and Feridun (2016) have reported that corruption is a grabbing hand which discourage FDI inflow. However, the works of Khan and Akbar (2013), Bellos and Subasat (2012), Quazi, Vemuri and Soliman (2014), Kolstad and Wiig (2013), Yang et al (2018), Różański and Sekuła (2016), Bellos (2013), Fung andGracia-Herrero (2012) and Helmy (2013) have submitted that corruption is ...…”
Section: Corruption and Foreign Direct Investmentmentioning
confidence: 99%
“…In addition, most of the studies utilized Ordinary Least Squares (OLS) technique, while some deployed Generalized Method of Moments (GMM) and other econometrics methods. For example, Osabutey and Okoro (2015), Nnadi and Soobaroyen (2015), De Beule and Duanmu (2012), Amarandei (2013), Jeong (2014), Azam and Ahmad (2013), Gani and Al-Abri (2013), Epaphra and Massawe (2017), Anyanwu (2012), Hossain and Rahman (2017), Godinez and Liu (2015), Saidi, Ochi and Ghandri (2013), Okafor (2015), Różański and Sekuła (2016), Udenze (2014), Alemu (2012), Smarzynska and Wei (2000), Erdogan and Unver (2015), Cleeve (2012), Gobinder andHaider (2014), Hakkala et al (2008), Al-Khouri and Khalik (2013), Jadhav (2012), Bellos and Subasat (2012), Hoa and Lin (2016), Khan and Akbar (2013) and Kolstad and Wiig (2013) utilized OLS regression method in their analysis of the relationship between corruption and FDI I inflow.…”
Section: Corruption and Foreign Direct Investmentmentioning
confidence: 99%
See 2 more Smart Citations